Sunday

March 1, 2015

March 1, 2015

Posted by **Princess** on Tuesday, December 11, 2012 at 8:49am.

x - 2y = -3

simultaneous equation by elimination

- Math -
**Steve**, Tuesday, December 11, 2012 at 10:35amelimination is usually done with linear equations. Using substitution,

x = 2y-3, so we have

(2y-3)^2 + 9y^2 = 37

4y^2 - 12y + 9 + 9y^2 = 37

13y^2 - 12y - 28 = 0

(y-2)(13y+14) = 0

**Answer this Question**

**Related Questions**

math simultaneous equation with surds - ive got quite far but im stuck, can you ...

maths B - i dont understand how to do simultaneous solutions of linear functions...

Physics - Two events that are simultaneous in one frame of reference will be: A...

maths - simultaneous equations x + 2y = 4 3x - 4y = 7 x=3 and y = 1/2 i need to ...

math - solve the simultaneous equation 2x+2y=7 x^2-4y^2=8

math - how do you solve that pair of simultaneous equation^2=4-y x=y+3?

math - how do you solve that pair of simultaneous equation^2=4-y x=y+3?

math - how do you solve that pair of simultaneous equation^2=4-y x=y+3?

Math - please answer this simultaneous equation. 3a-b=9 2a+2b=14

math - answer this simultaneous equation please. 3a-b=9 2a+2b=14